Effect of growth rate on post mortem proteolysis in lamb muscles - Sylvestre M.N.; Feidt C.; Brun Bellut J. (Sheep and goat nutrition: Intake, digestion, quality of products and rangelands, 2000)
Proteolysis in Longissimus dorsi (LD) and Semi membranosus (SM), and particularly collagen degradation was studied to examine the effect of growth rate on proteolysis of 5 low growth rate lambs (LGR) and 5 high growth rate lambs (HGR). HGR lambs had significantly higher (P less than 0.05) live weights, carcass weights and growth rate. No significant differences were observed between muscles in non protein nitrogen (NPN) content, free hydroxyproline (OH-Proline) in fresh muscle (FM) or NPN, but LD had more total OH-Proline content than SM (758.49 mg N perg FM vs 721 mg N perg FM). NPN content at slaughtering was significantly higher (P less than 0.05) in HGR lambs. HGR lambs had significantly higher ante mortem proteolysis (plus 6 per cent) in the two studied muscles. NPN content increased about 15 per cent during storage until 21 days post mortem (it represented 1.5 per cent of total nitrogen).
8. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 1998/09/03-05, Grignon (France)